Rehabilitation improves the effectiveness of nusinersen in children with type 2 spinal muscular atrophy: pNF-H and muscle MRI as potential biomarkers - Sun, Yifan; Li, Wei; Cui, Xin; Li, Yang; Gao, Xiucheng; Fu, Dalin; Zhao, Xiaoke; Cao, Tong; Zhu, Min (Frontiers in Neurology, 2025)
IntroductionRehabilitation therapy is an important approach for spinal muscular atrophy (SMA) management. Currently, rare articles introduce that the combination of nusinersen and rehabilitation yields better results in SMA patients compared to using nusinersen alone. The present study examined whether rehabilitation therapy can improve the effectiveness of nusinersen and phosphorylated neurofilament heavy chain (pNF-H) and muscle magnetic resonance imaging (MRI) can serve as potential biomarkers for evaluating the therapeutic effects in type-2 SMA patients.MethodsThis observational study enrolled 22 pediatric patients with type-2 SMA. Enrolled patients were divided into two groups based on the rehabilitation treatment. Motor function and swallowing function were analyzed at baseline, 6, 10, and 14 months. The level of pNF-H and MRI of the thigh skeletal muscles were analyzed at baseline and 14 months.ResultsGreater improvement in motor function was observed in the rehabilitation group compared with the non-rehabilitation group. The levels of pNF-H in the serum and cerebrospinal fluid significantly decreased at 14 months. One patient from the rehabilitation treatment group showed mild improvement in the degree of fatty infiltration in the quadriceps muscles after 14 months.ConclusionThis study suggests that rehabilitation therapy improves the effectiveness of nusinersen on type-2 SMA patients, and the levels of pNF-H and skeletal muscle MRI can serve as potential biomarkers for evaluating the effectiveness of SMA treatment.